2003
DOI: 10.1046/j.1365-3148.2003.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and specificity of clinically significant red cell alloantibodies in Chinese women during pregnancy – a review of cases from 1997 to 2001

Abstract: Guidelines for the prevention and management of red cell alloantibodies during pregnancy, related to anti-D in particular, are well established in Caucasian populations. However, because of the racial difference of the blood group distribution, applicability to Chinese is unknown as a result of insufficient data on the prevalence and their outcome. In a retrospective review of 28,303 (21,327 Chinese) antenatal attendances from 1997 to 2001, 213 (0.79%) women were found to have a total of 230 irregular antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
2
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 12 publications
1
50
2
5
Order By: Relevance
“…Alloimmunization rates in antenatal females ranged from 0.4 to 2.71 % [8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Alloimmunization rates in antenatal females ranged from 0.4 to 2.71 % [8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Lacking prophylaxis, it is estimated that at least one in every six RhD-negative women delivering an RhD-positive baby would be at risk [53]. To understand the racial distribution of this burden, w15% of Caucasians, 3e5% of African-Americans, 8% Asian-Indians, and <1% of Asians have RhDnegative blood groups [50,54,55]. The prevalence of RhD-negative blood group in Europeans is relatively high, and varies between 11% and 21%.…”
Section: Rhesus Hemolytic Disease Of the Fetus And Newbornmentioning
confidence: 99%
“…Out of 2060 mothers, history of blood transfusion was present in 14 (0.7%) women but none had alloantibodies. Prevalence of alloimmunization among pregnant women documented in various published studies [8][9][10][13][14][15][16] and the present study is shown in Table 6.…”
Section: Methodsmentioning
confidence: 56%